Pretty poodle parlour - McAllister, Angela (London: Orion Children's Books, 2016)
Mimi loves helping out at the Pretty Poodle parlour, so when Madame Shampoodle leaves her niece, Florence, and Mimi in charge for the day, the girls can't wait to have the salon all to
Keywords: Children's stories